The Impact of Carbon Tax Policies in Achieving the Ambitious Target of Net Zero Emissions 2060 in G20 Countries - Wahyudi, Heru; Leny, Sandra Mei (International Journal of Energy Economics and Policy, 2025)
This research aims to explore the impact of carbon tax policies on reducing carbon emissions in G20 countries in achieving the ambitious target of Net Zero Emissions by 2060. This research uses the Pearson correlation test method and content analysis, the time period studied is 4 years. Based on data analysis, it is known that there is a negative and significant relationship between carbon taxes and carbon emission levels in G20 countries. These results support the hypothesis that carbon taxes are an effective policy instrument in reducing carbon emissions, where increasing carbon taxes has the potential to encourage substantial reductions in emissions. The effectiveness of carbon tax policies is influenced by the level of industrialization, commitment to environmental policy, and national strategy. Countries with higher carbon tax rates and consistent policy implementation, such as Japan and South Korea, have achieved more significant emissions reductions than countries with lower tax rates or limited implementation. This research emphasizes the importance of integrating carbon tax policies with a comprehensive climate change mitigation strategy, including investment in low-carbon technologies, increasing energy efficiency, and transitioning to renewable energy so that it can become an effective tool in directing the global economy towards environmental sustainability and achieving long-term climate targets long term, including Net Zero Emissions by 2060.